Relations between Job Satisfaction and Turnover of Offshore Medical Staff in Azerbaijan. - Bilandarli, Lala (ADA University, 2015)
This study explores the relationship between job satisfaction and the turnover of offshore medical doctors in the Caspian Sea. Turnover intention was measured as intent to leave the company within the next 12 months. Several factors relating to job satisfaction were grouped together in sub-groups: stress at work, physical risk of offshore environment, shift-work and long hours, distance from home, training opportunities and professional development in current organization, limitation of lifestyle offshore, and the relationship with supervisor. Correlation and point elasticity methods confirmed that promotion, training opportunities and salary are major drivers of job satisfaction. Environmental factors had the greatest negative correlation with job satisfaction: stress at work, limited lifestyle, and distance from home. A clear link has been demonstrated between lack of job satisfaction and turnover of offshore medical staff in Azerbaijan.
Keywords: Business; Human Resources.; Azerbaijan--Human Resources.